3 - Upper mantle structure of the Aegean derived from two-station phase velocities of fundamental mode Rayleigh waves - Kassaras, I.; Makropoulos, K.; Bourova, E.; H. Pedersen; Hatzfeld, D. (The South Aegean Active Volcanic Arc, 2005)
Fundamental mode Rayleigh waves generated by 380 teleseismic events were analyzed over the period range 10-100 s, in order to study the structure of the lithosphere and upper mantle of the Aegean region. Using the two-station method, 255 reliable phase velocity dispersion curves were calculated over 35 profiles and further inverted to obtain a new model of S-wave velocity with depth. S-wave velocities are resolved to a depth of 180 km. Important features are defined, such as a not completely amphitheatric geometry for the western (≈25° dipping angle) and eastern segments (≈35° dipping angle) of the subducted slab. In north Aegean, high velocities associate with the North Aegean Trough, which westernmost tip correlates with a high velocity anomaly in eastern continental Greece. This zone of high velocity contrast is extended in depth, dips southwards with an angle ≈350 and intersects with the subducted slab at an area where the direction of major tectonic axes changes from ENE-WSW to NNW-SSE towards the continental massif. In Central and North Aegean, where back arc extension and crustal thinning occur, the predominant low velocities observed could be interpreted by upper mantle high thermal flow and partial melting.
Keywords: Aegean region; dispersion; inversion; Rayleigh wave